The Endurance of Family Businesses : A Global Overview - Fernandez Perez, Paloma; Colli, Andrea (Cambridge : Cambridge University Press, 2013)
The Endurance of Family Businesses is a collection of essays offering an overview of the importance and resilience of family-controlled large businesses. Much of economic and business history research neglects family businesses, considering them an inefficient form of business organization. These essays discuss the strengths of family businesses: the ways family firms have managed, financed and governed their corporations, as well as the way in which they structure their relationship with the external environment, from the government to the company's stakeholders. Family businesses have learned new ways of organizing their resources and using their accumulated know-how for new markets and institutional environments. This volume combines the expertise of well-known scholars who specialize in business history, economic history, management and consulting, to provide an interdisciplinary perspective on family businesses. Contributors provide a global view by taking into account Asian, American and European experiences.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).